2016
DOI: 10.1007/s11999-015-4344-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface Damage Is Not Reduced With Highly Crosslinked Polyethylene Tibial Inserts at Short-term

Abstract: Background Highly crosslinked ultrahigh-molecularweight polyethylene (XLPE) has been shown to reduce wear in hip arthroplasty, but the advantages over conventional polyethylene (PE) in total knee arthroplasty (TKA), if any, remain unclear. Questions/purposes Do differences exist in (1) surface damage as measured by damage score and percent area affected; and (2) extent and location of dimensional changes between XLPE and conventional PE observed on retrieved TKA tibial inserts?Methods In this study of componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Peak oxidation index greater than 1 leads to variability in mechanical properties. XLPE highly crosslinked ultrahigh-molecular-weight polyethylene, compPE compression-molded polyethylene previously reported; however, the same trend was found as in the shorter-term retrieved inserts-namely, the largest reduction in crosslink density occurred at the loaded surface region [15]. Decreased crosslink density with implantation time has been postulated to be caused either by mechanical means with tensile stresses near the surface reaching sufficient magnitudes to break crosslinks between the polyethylene chains or by chemical means through the absorption of lipids into the polyethylene, which could also be greater in highly stressed regions of the material [18].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Peak oxidation index greater than 1 leads to variability in mechanical properties. XLPE highly crosslinked ultrahigh-molecular-weight polyethylene, compPE compression-molded polyethylene previously reported; however, the same trend was found as in the shorter-term retrieved inserts-namely, the largest reduction in crosslink density occurred at the loaded surface region [15]. Decreased crosslink density with implantation time has been postulated to be caused either by mechanical means with tensile stresses near the surface reaching sufficient magnitudes to break crosslinks between the polyethylene chains or by chemical means through the absorption of lipids into the polyethylene, which could also be greater in highly stressed regions of the material [18].…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, concern exists that XLPE may be associated with increased oxidation, reduced mechanical strength, decreased yield strength, and decreased toughness. These drawbacks are of particular concern in posterior-stabilized designs, given the risk of fracture of the polyethylene tibial post [4,8,12,14,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…The regions on which they were present were manually replicated onto the digital images using Photoshop CS2 software (Adobe Systems, San Jose, CA, USA) to quantify the area of damage for each mode on both medial and lateral plateaus. This damage mapping technique has been described in more detail elsewhere [10,24]. Burnishing was the most prevalent damage mode on the PE articular surface and was considered the in vivo-loaded contact area with the surface of the metallic femoral component while the insert had been implanted in the patient.…”
Section: Identification Of the Regions To Be Testedmentioning
confidence: 99%
“…In contrast, clinical reports with mid-term followup such as those from the Kaiser Implant Registry [18] demonstrated no benefits or differences in revision surgery rates between TKAs with crosslinked PE versus conventional polyethylene inserts [19,20,28]. In a recent shortterm implant retrieval study comparing retrieved crosslinked PE and conventional polyethylene TKA inserts, Liu et al found no difference in polyethylene surface damage between the two materials [24]. However, surface damage does not preclude the possibility that a difference in wear and creep might still exist [34].…”
Section: Introductionmentioning
confidence: 99%
“…10 These findings might explain the difficulties encountered by surgeons. A modified 3D comparison method developed in a previous prosthetic evaluation study by our group 31 was applied for comparisons between the femoral stems and the medullary canal models. Advantages of such a method are the ability to obtain quantitative results and use color maps during visualization.…”
Section: Discussionmentioning
confidence: 99%